(untitled) (Research, Society and Development, 2022)
Due to their attractive properties, plant extracts from the Amazon region have made them fundamental raw materials for the manufacture of cosmetic products on the world market. In the creation and development of new products, factorial planning presents itself as an efficient scientific tool to be used. Thus, the objective of this work was to carry out the development of a liquid soap combining the plant extracts of mulateiro and andiroba, since there is no knowledge of any product that combines the actions of both, with the aid of statistical experimental planning. With this statistical tool, it was possible to evaluate the influence of the main components of the formulation (lauryl, amide, amphoteric, plant extract and essence) on the physicochemical properties of the product. After the experimental development, it was found that the proposal to create a liquid soap using two extracts is viable, as there was no physical-chemical imbalance promoted by the combination in the developed formulations. In turn, the factorial design analysis demonstrates that lauryl (sodium lauryl ether sulfate) influenced the following responses: pH, electrical conductivity, viscosity, density and dry residue. The amide (coconut fatty acid diethanolamine) was significant for pH, viscosity and dry residue. The amphoteric component (bezainic amphoteric) influenced the responses to viscosity, density and dry residue. In turn, the essence was significant only for the dry residue response. Finally, the plant extract in the formulations did not show statistical significance in the responses obtained.